PELATIHAN PRODUKTIF DI MASA PANDEMI DI DESA TANI MULYA NGAMPRAH, KABUPATEN BANDUNG BARAT, JAWA BARAT : Productive Training during the Pandemic in Tani Mulya Village Ngamprah, West Bandung Regency, West Java - Asmat Purba; Lusi Marlina; Suharto; Eva Damayanti (PUAN INDONESIA, 2023)
The Corona Virus Desease 2019 (Covid-19) epidemic has had a significant impact on economic growth in Indonesia. The community service program was carried out in the Central Overtime Village RW 18, Tani Mulya Village, Ngamprah District, West Bandung Regency, Weat Java, which aims to empower the community's economy by providing counseling and workshops on making liquid soap and making hand sanitizer in order to increase the selling value of ingredients for additional improvement of the people's economy. Meanwhile, the uses obtained from the implementation of community service include; able to provide awareness to local residents of the importance of the value of creativity and creative economy by providing added value to raw materials, and being able to become an additional source of income as the development of entrepreneurship and reducing the unemployment rate of the community. The methods used in this community service activity are counseling, demonstration and training to the community as well as assisting in the processing of raw materials for making liquid soap and hand sanitizer. The results of the activity showed the enthusiasm of the residents in participating in the counseling and workshop, being able to provide awareness to residents, which is very important to participate in the development of the creative economy of entrepreneurship in improving the economy of residents.